If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -17 = x + 69 Reorder the terms: -17 = 69 + x Solving -17 = 69 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -17 + -1x = 69 + x + -1x Combine like terms: x + -1x = 0 -17 + -1x = 69 + 0 -17 + -1x = 69 Add '17' to each side of the equation. -17 + 17 + -1x = 69 + 17 Combine like terms: -17 + 17 = 0 0 + -1x = 69 + 17 -1x = 69 + 17 Combine like terms: 69 + 17 = 86 -1x = 86 Divide each side by '-1'. x = -86 Simplifying x = -86
| 89=-64+w | | y-(-3)=9 | | 15=-18+a | | 25=8*6+b | | 12=3-(-1y) | | c+31=-3 | | a-22=-1 | | p=18(-64) | | 2+3(x+6)=11-(5x+15) | | 1.8r+9=-5 | | s-44=-36 | | 4b^2w^3/3c^2k+5x^2/6b^3k^2 | | 1*y=2 | | 216-5x=31x+20 | | 18=-21+y | | 45x+78=x^2 | | c-16=-79 | | p=-5(18) | | 55=81+x | | 0=-3-(-1y) | | 4t+3=t-3 | | 0y-(-1)=1 | | p=-6(18) | | 2(4b+1)=50 | | -91=9p+8 | | 91=9j+8 | | -91=9l | | p-18=18(6) | | p+18=18(-6) | | x^2+8x-7=-13+2 | | p-18=18(-6) | | p-18=23/3(-6) |